2020
DOI: 10.1177/1096348020957072
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Snowmaking: Winter Sports Between State-Owned Company Policy and Tourist Demand

Abstract: Due to changing climatic conditions, artificial snowmaking has become a major method of ski resort adaptation globally. It is a financially intensive operation requiring high start-up investment and involving operating costs that are dependent on weather conditions. Operational costs and the expansion of artificial snowmaking systems increase the price of ski passes. In our work, we analyzed the operations of a public company that operates the largest ski resorts in Serbia and directs the flow of winter sports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Challenges arise with wastewater discharge, partly controlled and partly spontaneous, leading to environmental degradation. Regarding our study area, several studies confirm the negative impact of intensive winter tourism development on water quality, especially in terms of the physico-chemical composition of water and the condition of watercourses [72,126], as well as water consumption [127].…”
Section: Conflict: Ski Area-protection and Use Of Watermentioning
confidence: 52%
“…Challenges arise with wastewater discharge, partly controlled and partly spontaneous, leading to environmental degradation. Regarding our study area, several studies confirm the negative impact of intensive winter tourism development on water quality, especially in terms of the physico-chemical composition of water and the condition of watercourses [72,126], as well as water consumption [127].…”
Section: Conflict: Ski Area-protection and Use Of Watermentioning
confidence: 52%
“…To increase the number of tourists, related transportation, such as domestic and international air transport [35], as well as investment in infrastructure for artificial snow, also plays an important role [36].…”
Section: Categories Objectivementioning
confidence: 99%
“…First, many studies have investigated the topic of ski resorts from economics, finance, and business perspectives. Various sets of factors were introduced into the ski resorts' performances, profits, and pricing, and demands prediction problems, such as resorts' facilities [6,34], snow conditions [9,[34][35][36][37][38], slope conditions [6,9,34], altitudes [6], prices [37][38][39][40][41][42], weather [8,10,20,22,35,40,41,43,44], policy strategies [4,21], original country GDP [2,36,38], time period or season [10,36,43,45], consumer income [10,40], local economy [9], distance or location [6,46], transportation or related costs [10,34], and other consumer characteristics [8,9,47].…”
Section: Ski Tourism Researchmentioning
confidence: 99%
“…Prior studies have shown that the demand, performance, and development of ski resorts are influenced by multi-aspect factors, such as service quality, time, transportation, local development, natural resources, climate, economy, and skiers' characteristics [2,[6][7][8][9][10], which revealed the complicated nature of the ski resort industry. However, in terms of the skiers' experiences perspective, most studies have only focused on single-aspect factors, such as service quality attributes or subjective experience [11][12][13].…”
Section: Introductionmentioning
confidence: 99%